Phosphorus uptake by rice from soil that is flooded, drained or flooded then drained - Huguenin-Elie, O.; Kirk, G.J.D.; Frossard, E. (Wiley, 2003)
To investigate the mechanisms by which rice plants growing in alternately flooded and drained soils absorb soil phosphate, we grew rice in moist, flooded and flooded then moist soils, and compared the measured uptake of phosphorus (P) with that calculated using a mathematical model of uptake allowing for solubilization by various means. The theory and equations for the model are given, together with a method for solving diffusion equations near roots in a root system of increasing density. The diffusion coefficients and buffer powers of P in the soil under the different water regimes are measured by following diffusion of P to a resin sink, and the parameters describing solubilization are estimated from previously published results. In all the water regimes studied, the plants relied upon solubilization for most of their P. The roots were not mycorrhizal, as they will often not be in intermittently flooded soils. In the flooded soil, uptake was three times that in the moist soil, and was consistent with solubilization by acidification caused by roots as a result of oxidation of iron and imbalance between the intake of cations and anions. In the moist soil, the uptake was consistent with solubilization by excretion of organic anions from the roots. In the flooded then moist soil, uptake declined sharply as the soil dried because P became immobilized in the soil. However, the final uptake was similar to that in the continuously moist soil, indicating that some of the immobilized P was re‐solubilized by roots, possibly by excretion of organic anions.